Effects of the COVID-19 Pandemic on Chinese Graduate Students’ Learning Activities: A Latent Class Analysis - Wang, Jinqing; Liang, Zhengyan; Zhang, Minqiang; Kang, Derong; Zeng, Qing (Frontiers in Psychology, 2022)
To investigate the impact of the pandemic on graduate students’ learning activities, questionnaires were distributed to graduate students in universities across China, and 2,818 responses were collected. The analysis identified four latent classes: “the overall less affected” (34.83%), “the overall more affected” (31.97%), “course activities were more affected” (19.40%) and “social activities were more affected” (13.79%). Next, a multinomial logistic regression analysis was conducted. The results indicated that during the pandemic, the learning activities of graduate students in all grades were affected to varying degrees, and the impacts on second-year and third-year graduate students were greater than those of first-year graduate students. The analysis of variance revealed that the scores for anxiety, depression and social anxiety of “the overall more affected” were significantly greater than those of the other three groups, and nearly one-third of students belonged to this class, suggesting that more attention and care should be given to these students. As a result of the COVID-19 pandemic, a number of graduate students have suffered mental problems (anxiety and depression). Under the current backdrop of a new normal, schools and teachers should pay attention to graduate students’ mental health, providing targeted assistance to different types of students.